Acquisition and loss of virulence-associated factors during genome evolution and speciation in three clades of Bordetella species. (December 2016) - Linz, Bodo; Ivanov, Yury; Preston, Andrew; Brinkac, Lauren; Parkhill, Julian; Kim, Maria; Harris, Simon; Goodfield, Laura; Fry, Norman; Gorringe, Andrew; Nicholson, Tracy; Register, Karen; et al.
Abstract Background The genusBordetella consists of nine species that include important respiratory pathogens such as the 'classical' speciesB. bronchiseptica, B. pertussis andB. parapertussis and six more distantly related and less extensively studied species. Here we analyze sequence diversity and gene content of 128 genome sequences from all nine species with focus on the evolution of virulence-associated factors. Results Both genome-wide sequence-based and gene content-based phylogenetic trees divide the genus into three species clades. The phylogenies are congruent between species suggesting genus-wide co-evolution of sequence diversity and gene content, but less correlated within species, mainly because of strain-specific presence of many different prophages. We compared the genomes with focus on virulence-associated genes and identified multiple clade-specific, species-specific and strain-specific events of gene acquisition and gene loss, including genes encoding O-antigens, protein secretion systems and bacterial toxins. Gene loss was more frequent than gene gain throughout the evolution, and loss of hundreds of genes was associated with the origin of several species, including the recently evolved human-restrictedB. pertussis andB. holmesii, B. parapertussis and the avian pathogenB. avium . Conclusions Acquisition and loss of multiple genes drive the evolution and speciation in the genusBordetella, including large scale gene loss associated with the origin of several species. Recent loss and functional inactivation of genes, including those encoding pertussis vaccine components and bacterial toxins, in individual strains emphasize ongoing evolution.